Gastrointestinal Health Risk Analysis of Marine Pollution in the Java Coast: Biomarkers of Exposure in a Fishing Community in Semarang - Aulia Zikra; Megawati; Fitriani Abdal; Yusriati; Diana Chandra Dewi (CV. Get Press Indonesia, 2025)
This study aims to assess the relationship between marine pollution exposure levels and the risk of gastrointestinal health disorders in coastal fishing communities in Semarang City, Indonesia. A cross-sectional study was conducted from May to October 2025 in the Tambaklorok and Tanjung Emas areas, which are areas with high seafood consumption patterns and exposure to marine environments. Data were collected through a structured questionnaire covering respondent characteristics, seafood consumption habits, and gastrointestinal complaints using the Gastrointestinal Symptom Rating Scale (GSRS). All respondents (100%) tested positive for microplastic exposure in feces with an average concentration of 18.4 6.7 particles/gram, dominated by PE, PP, and PS polymers, as well as heavy metal levels (Hg, Pb, Cd) through AAS or ICP-MS. Microplastics were the strongest predictor of increased GSRS scores (=0.37, p0.001), followed by blood mercury levels and inadequate sanitation conditions, with the model able to explain 43-47% of the variation in symptoms. This research fills a gap in the literature regarding marine pollution risk in Indonesia and provides a scientific basis for developing environmental health policies, coastal waste management, and more targeted public health intervention programs for fishing communities.